Frankenstein in Baghdad : a novel - Saʻdāwī, Aḥmad (Penguin Books, 2018)
After he constructs a corpse from body parts found on the street, Hadi wants the government to prepare a proper burial, but when the corpse goes missing, a series of strange murders occur and Hadi realizes he has created a monster.